Speech Act of Indonesian Stand Up Comedian that Potentially Implicated to Racist Problem (Linguistic Forensic Analysis) - Nini Ibrahim; Ummul Qura; Fauzi Rahman (Humanus, 2020)
Indonesia has been made busy by the circulation of video footage showing the stand up comedian (komika) in a stand up comedy event that offend SARA (ethnicity, religion, ancestry, and group of people). The purpose of this study was to analyze the komika’s materials using forensic linguistic analysis with functional pragmatic approaches. The method used in this research is descriptive qualitative with functional pragmatic analysis using data analysis techniques (1) speech illocution analysis, (2) speech implicature, and (3) level of speech validity. The results showed that the illocutionary power and implicature of the identified komika could fulfill the elements of leading opinion as an expression offending SARA. On the illocutionary power of speech, it is classified that an indicated declarative and expressive speech can potentially offend the speech partner. Moreover, if the diction is used in the speech, it raises the issue of SARA.